Adsorption of Bovine Serum Albumin on Silver Nanoparticle Layer Deposited on Mercaptohexylpyridinium‐Coated Quartz Crystal Microbalance with Dissipation Gold Electrode: Studied by Electrochemical Quartz Crystal Microbalance with Dissipation. Issue 13 (4th February 2020) - Seumo Tchekwagep, Patrick Marcel; Eminovski, Jildiz Hamit; Nanseu-Njiki, Charles Péguy; Ngameni, Emmanuel; Arnebrant, Thomas; Ruzgas, Tautgirdas
Abstract : Increasing use of silver nanoparticles (AgNPs) in different consumer products provokes interest in understanding interactions of AgNPs with biological molecules, e.g., proteins. The adsorption of AgNPs and bovine serum albumin (BSA) onto self‐assembled monolayer of mercaptohexylpyridinium (MHP) on gold surface is described. A quartz crystal microbalance coupled with electrochemical measurements are used to study interactions between AgNPs and BSA. It is found that AgNPs adsorbed on MHP can be considered as highly elastic (stiff) film as the dissipation Δ D  ≈ 0. Measurements of the mass loss and the increase in dissipation in parallel with the electrochemical oxidation/reduction of AgNPs shows that albumin adsorption on AgNPs highly diminish electrochemical Ag/AgCl conversion. The formation of a less rigid Ag layer than the original MHP‐AgNPs film is also indicated. The 3D assemblies of nanostructures observed with scanning electron microscopy (SEM) reveal clustering of particles after the redox process. Abstract : Herein, the interactions between silver nanoparticles (AgNPs) and bovine serum albumin (BSA) using quartz crystal microbalance with dissipation (QCM‐D) coupled with electrochemistry are discussed. It is found that the mass loss and the increase in dissipation in parallel with the electrochemical oxidation/reduction of AgNPs shows that albumin adsorption on AgNPs highly diminish electrochemical Ag/AgCl conversion.